PENGARUH SOCIAL MEDIA MARKETING, ELECTRONIC WORD OF MOUTH DAN PERSEPSI HARGA TERHADAP EKUITAS MEREK SERTA IMPLIKASINYA PADA PERILAKU KEPUTUSAN MASUK SD HARAPAN MULIA KOTA BEKASI - Claudius Hendra Agatama; Subagiyo; Yosi Stefhani (Pasca Sarjana Universitas Satya Negara Indonesia, 2023)
This research was conducted with the aim of analyzing the influence of social media marketing, electronic word of mouth and price perceptions on brand equity and their implications for the behavior of the decision to enter SD Harapan Mulia Bekasi City. The research sample was the parents of students who attended S D Harapan Mulia City of Bekasi with a total of 171 respondents. Quantitative descriptive research method, data analysis using Structural Equation Modeling with SmartPLS 3. The results showed that partially social media marketing, electronic word of mouth and price perceptions had a positive and significant effect on brand equity and the decision to enter SD Harapan Mulia Bekasi City. Brand equity has a positive and significant effect on the decision to enter SD Harapan Mulia, Bekasi City. Brand equity can mediate the relationship between social media marketing, electronic word of mouth and price perceptions with the decision to enter SD Harapan Mulia, Bekasi City.